2017
DOI: 10.1097/njh.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Interactions to Alleviate Psychological Symptoms in Patients Receiving Mechanical Ventilation

Abstract: Mechanical ventilation is a common life support intervention for critically ill patients that can cause stressful psychological symptoms. Animal assisted interactions have been used in variety of inpatient settings to reduce symptom burden and promote overall well-being. Due to the severity of illness associated with critical care, use of highly technological equipment, and heightened concern for infection control and patient safety, animal-assisted interaction has not been widely adopted in the intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The use of animals is now appearing in therapeutic settings, such as emergency departments [82], acute and hospice care [83,84], and elementary schools [42,85]. An ever-expanding area is the use of animals to prevent or diagnose health issues, such as detecting pathogens in the environment [86,87] or diagnosing cancers [88,89,90].…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…The use of animals is now appearing in therapeutic settings, such as emergency departments [82], acute and hospice care [83,84], and elementary schools [42,85]. An ever-expanding area is the use of animals to prevent or diagnose health issues, such as detecting pathogens in the environment [86,87] or diagnosing cancers [88,89,90].…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…Stay et al (2005) found that acupressure therapy, a form of massage therapy, was effective in improving the symptoms of dyspnea and anxiety in patients who required prolonged mechanical ventilation [15]. Examples of other non-pharmacological therapies that seem to be useful in reducing patients' anxiety during mechanical ventilation include music intervention [16] and animalassisted interactions [17]. Thus, by decreasing patient agitation and anxiety, nonpharmacological therapies may have the potential to reduce the length of ventilation and the associated complications.…”
Section: Introductionmentioning
confidence: 99%